Free-radical Scavenging properties and Cytotoxic Activity Evaluation of Latex C-serum from Hevea brasiliensis RRIM 600 - Kerche-Silva, Leandra Ernst; Cavalcante, Dalita Gomes Silva Morais; Danna, Caroline Silva; Gomes, Andressa Silva; Carrara, Iriana Moratto; Cecchini, Alessandra Lourenço; Yoshihara, Eidi; Job, Aldo Eloizo (Free Radicals and Antioxidants)
Background: There are few studies exploring the antioxidant properties of the latex C-serum of the Hevea brasiliensis latex and their possible use for therapeutic application. Objective: This study investigated the in vitro antioxidant activity of the latex C-serum of H. brasiliensis and assessed the cytotoxicity of this fraction in two human cell lines derived from normal tissue (MRC-5 and CCD 1059sk. Chemical characterization was also assessed. Methods: Latex from H. brasiliensis was centrifuged and the C-serum phase was tested for in vitro free radical scavenging assays, such as hydroxyl and nitric oxide radicals, hydrogen peroxide and total antioxidant capacity by the phosphomolibdate method. Latex C-serum was also investigated for cytotoxic properties by the MTT test. Latex C-serum was chemical characterized by Infrared Spectroscopy Fourier Transform (FTIR). Results: Latex C-serum effectively scavenged hydroxyl and nitric oxide radicals and hydrogen peroxide and presented potent antioxidant activity. The results were compared to ascorbic acid, a standard antioxidant. The cytotoxicity evaluation of latex C-serum demonstrated cell line dependency and for CCD 1059sk cells derived from skin fibroblasts, latex C-serum was not cytotoxic. FTIR showed the presence of proteins in latex C-serum. Conclusion: Latex C-serum from Hevea brasiliensis presented strong antioxidant potential and these results openthe possibility of further studies aiming the use of latex C-serum as treatment for skin diseases related to reactive oxygenspecies or skin preventive pharmacological formulations.
Keywords: Latex C-serum; Antioxidant; Hevea brasiliensis; FTIR; Cell viability